AB1078 RED CELL DISTRIBUTION WIDTH (RDW) – A NEW POSSIBLE DISEASE ACTIVITY PREDICTOR IN RELAPSING POLYCHONDRITIS. (June 2019) - Balan, Bianca; Gutiu, Roxana Ioana; Mustățea, Felicia; Felea, Ioana; Filipescu, Ileana; Pamfil, Cristina; Bene, Liliana; Rednic, Simona; Damian, Laura
Abstract : Background: Relapsing polychondritis (RP) is a rare condition defined by recurrent inflammation of cartilaginous tissue and systemic manifestations. Biomarkers for RP diagnosis and assessment of disease activity, damage and prognostic in clinical practice are currently lacking. Red blood cell distribution width (RDW) is an index of erythrocyte size variation depicting anizocytosis. RDW is routinely assessed, is not influenced by infections and its standard deviation (RDW-SD) does not depend on medium corpuscular volume. Recent studies showed an increased RDW in various autoimmune diseases (systemic lupus erythematosus, Sjogren's syndrome, rheumatoid arthritis, systemic vasculitis), correlating with inflammatory markers and disease activity. Also, the RDW seen in solid tumors and hematological cancers has prognostic value. Objectives: To asses the RDW-SD in RP patients, its relation with the disease activity and with the presence of neoplasia Methods: We performed a retrospective study on the patients diagnosed with RP in a tertiary Rheumatology department between January 2017 and January 2019, using the Atlasmed data management system of the institution. The concomitant diseases and the inflammation parameters were recorded. The RP activity was measured using RPDAI (relapsing polychondritis disease activity index). The correlation between variables were calculated using GraphPad Prism. Results: We identified 20 patients, median age 59.04 years (range 38-81), with a male-to-female ratio of 1: 5.66. An associated autoimune disease (Sjogren syndrome, Hashimoto thyroiditis, systemic lupus erythematosus, rheumatoid arthritis, psoriatic arthritis) was found in 85% of pacients. Moreover, 40% of the pacients had various types of solid or hematologic neoplasia, including myelodysplastic syndrome. An elevated RDW-SD was seen in 90% of RP patients. The average RPDAI was 10.6 points. RDW-SD significantly correlated to RPDAI (p=0.0012). Of the inflammatory parameters, RDW-SD was not found to be related to ESR and CRP. RDW-SD increased with age, but no correlation was found between RPDAI and age. All pacients with neoplasia had abnormally high RDW-SD. Nevertheless, RDW-SD was not significantly different in RP patients with or without neoplasia (Mann-Whitney test, p=0.56). Conclusion: RP was frequently associated with other autoimune diseases, but also with neoplasia.The positive correlation of RDW-SD and RPDAI in RP suggests a possible new, clinically employable, biomarker of disease activity. References: [1] Arnaud L et al, Autoimmun Rev 2012; 12(2):204-9. doi:10.1016/j.autrev.2012.06.005. [2] Hu ZD, JLPM 2016, doi: 10.21037/jlpm.2016.10.02 Disclosure of Interests: None declared